2023
DOI: 10.1038/s41467-023-39782-x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 in free-ranging white-tailed deer in the United States

Abstract: SARS-CoV-2 is a zoonotic virus with documented bi-directional transmission between people and animals. Transmission of SARS-CoV-2 from humans to free-ranging white-tailed deer (Odocoileus virginianus) poses a unique public health risk due to the potential for reservoir establishment where variants may persist and evolve. We collected 8,830 respiratory samples from free-ranging white-tailed deer across Washington, D.C. and 26 states in the United States between November 2021 and April 2022. We obtained 391 sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 63 publications
0
35
1
Order By: Relevance
“…While the 7% wild-type SARS-CoV-2 neutralizing antibody seroprevalence observed among white-tailed deer in our study ( Figure 1B ) was lower than the 14-40% neutralizing antibody positivity found in other locations 10,23,28,30,32 , it was surprisingly high given the semi-restricted nature of the sampling sites. All six seropositive deer samples tested positive in duplicate.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…While the 7% wild-type SARS-CoV-2 neutralizing antibody seroprevalence observed among white-tailed deer in our study ( Figure 1B ) was lower than the 14-40% neutralizing antibody positivity found in other locations 10,23,28,30,32 , it was surprisingly high given the semi-restricted nature of the sampling sites. All six seropositive deer samples tested positive in duplicate.…”
Section: Discussioncontrasting
confidence: 81%
“…Few examples of secondary spillover of any pathogen have been reported, likely in part due to the many behavioral and host barriers a pathogen must overcome combined with the challenges of observing such dynamics 2 . Despite this, potentially due to broad susceptibility and substantial exposure opportunities, several instances of SARS-CoV-2 secondary spillover have been reported including from farmed mink ( Neovison vison ) to workers in the Netherlands, imported golden hamsters ( Mesocricetus auratus ) to pet shop workers in Hong Kong, and white-tailed deer ( Odocoileus virginianus ) to human contacts in Canada and the United States 710 . Not all animals are equally likely to experience viral spillback, sustained transmission, and/or secondary spillover.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diluted serum samples were mixed in a 1:1 v/v ratio with a solution containing 1300 plaque-forming units per mL (PFU/mL) of SARS-CoV-2 Delta virus strain USA-GNL-1205/2021 (a generous gift from the World Reference Center for Emerging Viruses and Arboviruses), or approximately 40 PFU’s per well. Our serum samples were collected in June and July of 2022, following the Delta wave in fall of 2021, and given the life expectancy of the animal species (Supplementary Table 12) we were sampling, we assumed Delta would have been the most likely recent variant they were exposed to 54 . Each sample was tested in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Newly emergent VOCs generally perch atop a long ancestral phylogenetic branch, rooted in a historic lineage absent from the current variant landscape [6] . While SARS-CoVspillover/spillback to and from an animal host could potentially generate similar long phylogenetic branches [10] , recent evidence suggests that immunocompromised individuals with persistent infections are the main source of these divergent lineages [2,11] . Since the early stages of the pandemic, long-term replication has been documented in chronically infected immunocompromised individuals, accelerating intrahost viral evolution and leading to the acquisition of amino acid changes that often overlap with those identified in VOCs [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%